Saccharomyces cerevisiae Genome-Wide Mutant Screen for Sensitivity to 2,4-Diacetylphloroglucinol, an Antibiotic Produced by Pseudomonas fluorescens - Kwak, Youn-Sig (American Society for Microbiology (ASM), 2011)
2,4-Diacetylphloroglucinol (2,4-DAPG), an antibiotic produced by Pseudomonas fluorescens, has broad-spectrum antibiotic activity, inhibiting organisms ranging from viruses, bacteria, and fungi to higher plants and mammalian cells. The biosynthesis and regulation of 2,4-DAPG in P. fluorescens are well described, but the mode of action against target organisms is poorly understood. As a first step to elucidate the mechanism, we screened a deletion library of Saccharomyces cerevisiae in broth and agar medium supplemented with 2,4-DAPG. We identified 231 mutants that showed increased sensitivity to 2,4-DAPG under both conditions, including 22 multidrug resistance-related mutants. Three major physiological functions correlated with an increase in sensitivity to 2,4-DAPG: membrane function, reactive oxygen regulation, and cell homeostasis. Physiological studies with wild-type yeast validated the results of the mutant screens. The chemical-genetic fitness profile of 2,4-DAPG resembled those of menthol, sodium azide, and hydrogen peroxide determined in previous high-throughput screening studies. Collectively, these findings indicate that 2,4-DAPG acts on multiple basic cellular processes.